REGULATION OF FAMILY LAW AT THE INTERNATIONAL AND EUROPEAN LEVEL, WITH A SPECIAL FOCUS ON THE RIGHT TO HEALTH OF THE CHILD - Samardžić, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Family law represents a specific branch of law, given the sensitivity of the relationships which it mainly regulates. It is the reflection of the various influences acting on a given area and often, the differences between countries in the regulation of certain issues can be extremely large. Consequently, attempts to harmonize the rules of family law, especially to unify them, so far have largely been unsuccessful. However, progress can be observed on both, the international and European level. This paper will try to show the most important international and European bodies and within them, instruments issued with the aim of regulating matters falling within the area of ​​family law. In addition, the paper will be made special reference to the part of family law relating to children’s rights, namely on the right to health of the child as a basic right, without which other children’s rights are meaningless.